Design, optimization of bio flexible films of sumatriptan succinate and naproxen sodium via oro trans soft palatal delivery - Srishti Morris; Ashutosh Badola; Nidhi Gairola; Mahendra Prajapati (Creative Pharma Assent, 2026)
Background: Bio-flexible films are polymeric drug delivery systems designed to enhance systemic drug absorption through the oral mucosa. This study aimed to develop and optimize bio-flexible, mucoadhesive films containing Sumatriptan Succinate and Naproxen Sodium for oro-trans soft-palatal delivery. The drug combination provides rapid and sustained therapeutic effects for migraine management. Methodology: Bio-flexible films were prepared by solvent casting using hydroxypropyl methylcellulose (HPMC E15), HPMC K100, and glycerine. A Box–Behnken Design was employed to optimize the formulation by evaluating three independent variables and five dependent responses. Films were characterized for thickness, surface pH, folding endurance, disintegration time, swelling index, drug content, ex vivo permeation, and in vitro drug release. Drug release kinetics were analyzed using mathematical models. Results and Discussion: All formulations exhibited satisfactory physicochemical and mechanical properties. The optimized formulation showed a disintegration time of 153 s, with cumulative drug release of 96.33% for Sumatriptan Succinate and 94.00% for Naproxen Sodium within 40 min. The optimized film demonstrated adequate mechanical strength, uniform drug content, acceptable swelling behavior, and enhanced ex vivo permeation. Drug release followed the Higuchi and Korsmeyer–Peppas models. Conclusion: The optimized bio-flexible mucoadhesive film demonstrated rapid drug release and efficient ex vivo permeation, indicating its potential as a patient-friendly platform for oro-trans soft palatal delivery of Sumatriptan Succinate and Naproxen Sodium. Further in vivo studies are required to confirm its clinical potential.